2014
DOI: 10.1007/s12374-014-0330-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of mitochondria-localized carbonic anhydrase activity resulted in an increased biomass accumulation in Arabidopsis thaliana

Abstract: Carbonic anhydrase (CA; EC 4.2.1.1) catalyzes the interconversion of CO 2 and HCO 3 − and plays an important role in photosynthetic carbon assimilation. We report that the effect of manipulating AtβCA6 expression on the growth and biomass accumulation of Arabidopsis thaliana shows that AtβCA6 was expressed in mitochondria. Overexpression of AtβCA6 increased the fresh weight, dry weight and rosette leaf area and it was also linked to a slight decrease in the rate of respiration. By contrast, when the respiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…In addition, Hu et al (2010) presented evidence showing high expression of bCA2 and bCA4 in mesophyll cells, whereas bCA3 had very low expression in mesophyll cells, while Wang et al (2014) reported very low bCA3 expression in leaves with promoter::GUS studies. Since the other CAs that show significant expression are either in the chloroplast (Fett and Coleman, 1994;Villarejo et al, 2005;Fabre et al, 2007;Burén et al, 2011;Hu et al, 2015) or mitochondria (Fabre et al, 2007;Jiang et al, 2014), we conclude that bCA2 and bCA4 are the most abundant CA isoforms in the cytoplasm. This contention is supported by leaf RNAseq data (Table I), GUS staining (Fig.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In addition, Hu et al (2010) presented evidence showing high expression of bCA2 and bCA4 in mesophyll cells, whereas bCA3 had very low expression in mesophyll cells, while Wang et al (2014) reported very low bCA3 expression in leaves with promoter::GUS studies. Since the other CAs that show significant expression are either in the chloroplast (Fett and Coleman, 1994;Villarejo et al, 2005;Fabre et al, 2007;Burén et al, 2011;Hu et al, 2015) or mitochondria (Fabre et al, 2007;Jiang et al, 2014), we conclude that bCA2 and bCA4 are the most abundant CA isoforms in the cytoplasm. This contention is supported by leaf RNAseq data (Table I), GUS staining (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…More recently, Jiang et al (2014) reported that plants lacking the mitochondrial bCA6 grew slowly on low CO 2 . There have been few studies of other CA isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the expression of mitochondria-localized CA increased when the respiration rate of leaves decreased. Moreover, with an increase in the expression of CA activity, shoot biomass accumulated in Arabidopsis thaliana [18]. In our previous report [19], we found that microalgae promote the dissolution of limestone.…”
Section: Introductionmentioning
confidence: 67%
“…Using a method based on stable carbon isotopes, we quantified the proportion of bicarbonate use by plants [11]. Although the conversion to biomass from bicarbonate by the activity of CA has been proposed in studies of plant biomass production for energy [17,18,20], the mechanism and the capacity for bicarbonate use in plants in karst habitats are not fully understood. In this study, we hypothesized that CA activity of plants increased under drought stress, which produced H 2 O and CO 2 from the bicarbonate (HCO 3 − ) in limestone dissolution of karst soils for use in photosynthesis and biomass production.…”
Section: Introductionmentioning
confidence: 99%